Polarimetric SAR Modelling of a Two-Layer Structure - Al-Kahachi, Noora (Technical University of Munich, 2013)
The work contributes to the interpretation of quad polarimetric SAR data over (shallow) subarctic lakes, on the purpose of investigating SAR capabilities in revealing facts about the subsurface. For this, a model for the polarimetric backscattering from a two-layer structure observed by a fully polarimetric side looking synthetic aperture radar at low frequency (L-Band) is developed. The model simulations are compared to data obtained by ALOS-PALSAR over frozen shallow subarctic lakes acquired over several regions in the northern wetlands. Die vorliegende Arbeit liefert einen Beitrag zur Interpretation voll polarimetrischer SAR-Daten von (flachen) subarktischen Seen mit dem Zweck, das Potenzial in der Ermittlung von Eigenschaften von unter der Oberfläche gelagerter Schichten aufzudecken. Dazu wird ein Modell der polarimetrischen Rückstreuung einer zweischichtigen Struktur erarbeitet, wie sie auch mit einem seitlich blickenden Radar mit synthetischer Apertur bei niedrigen Frequenzen (L-Band) gemessen wird. Das Modell wird mit SAR-Daten verglichen, die vom ALOS-PALSAR System über den nördlichen subarktischen Regionen aufgenommen wurden.